Strategic Approach for Increasing Innovation Capacity of the SMEs - Angeloska-Dichovska, Monika; Boshkoska, Meri; Angeleski, Marjan (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
Abstract: Small and medium-sized enterprises (SMEs) are crucial for any national economy through their vital contribution to sustainable growth, economic development and employment. The digital revolution, globalization, and the latest impact and pressure caused by the Covid-19 pandemic have posed even greater barriers and challenges for these enterprises. In order for small and medium-sized enterprises to respond to the new challenges, to participate in the market and gain a competitive position, they need to be different, and this can only be accomplished through an innovative way of working. To foster innovation, strategic changes are needed in the operation of the SMEs, with a focus on the people involved, the ways and methods used in the organizational environment, and the desired innovation results. Connecting to the external environment (networking) and/or using an open innovation system are also fundamental to the success of the enterprise innovation process. Innovative capacity of the businesses is a function of the organization’s culture, resources and networks. The main purpose of this paper is to identify certain strategic factors that contribute to creating an innovative organizational environment and fostering innovation, i.e. increasing the innovation capacity of SMEs in Pelagonia region in North Macedonia.